Environmentally Friendly Silver Nanoparticle Synthesis Using Gandaria (Bouea macrophylla) Leaf Waste Extract for Mercury Detection in Facial Cream Products - Bramantyo Hario Nugroho; Juwarin Pancawati; Yus Rama Denny (Tecno Scientifica Publishing, 2026)
This study aimed to synthesize and characterize silver nanoparticles (AgNPs) using the stem bark extract of Gandaria (Bouea macrophylla) and to evaluate their selectivity for mercury (Hg) detection. The Gandaria stem bark was extracted using methanol as the solvent through the maceration method. Silver nanoparticles were synthesized using extract concentrations of 1%, 2%, and 4%. Characterization of the AgNPs using UV–Visible spectrophotometry showed that the highest absorbance was observed at the 4% extract concentration, whereas the lowest absorbance was recorded at the 1% concentration. The selectivity test demonstrated that the synthesized AgNPs were highly selective toward Hg in HgCl₂ solution compared with Pb in PbCl₂ solution and Ca in CaCl₂ solution. AgNPs synthesized using the 4% extract concentration could be used as a preliminary qualitative colorimetric detection material for identifying mercury in facial whitening creams available on the market. Based on Particle Size Analyzer (PSA) and Scanning electron microscopy with energy dispersive X-ray spectrometry (SEM–EDX) analyses, the AgNPs synthesized using the 4% Gandaria stem bark extract were confirmed to fall within the nanoparticle size range.